Digital radiography of interproximal caries: effect of different filters - Eickholz, Peter; Kolb, Ingo; Lenhard, Markus; Haßfeld, Stefan; Staehle, Hans Jörg (Caries research, 1999)
The aim of this study was to compare the effect of different image processing modes (filters) on reproducibility and validity of the assessment of interproximal carious lesions on digitized radiographic images. Standardized radiographs of 34 extracted teeth exhibiting interproximal caries were obtained. All radiographs were digitized and using the FRIACOM-software the central depth (CD) of each carious lesion was measured on the unchanged radiographic image and after use of five different filters with 7fold and 18fold magnification. All measurements were repeated after 1 week to estimate reproducibility. Histometric CD assessments provided a gold standard for comparison with the radiographic measurements (validity). Neither reproducibility nor validity of CD measurements were improved by one of the filters. Measurements of dentinal lesions showed a statistically higher variability than those of enamel lesions (p<0.001). 18fold magnification provided more valid CD measurements than 7fold magnification (p<0.001). In this study digital manipulations of radiographic images failed to result in statistically significantly improved reproducibility or validity of CD measurements.
Gesehen am 09.02.2021